The politics of planning in Eastern Cape local government: a case study of Ngqushwa and Buffalo City, 1998-2004 - Hollands, Glenn Delroy (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2007)
This thesis examines the political implications of the integrated development planning process embarked upon by South African municipalities in the period 1998-2004. Through the use of case study methodology that focuses on the Eastern Cape municipalities of Buffalo City and Ngqushwa, the conventions of municipal planning are examined. This inquiry into municipal planning draws upon official government documents and reports and publications from the nongovernment sector. The thesis is particularly focused on the claims made in policy documents and related secondary sources and compares these to more critical reports and publication as well as the author's personal experience of the integrated development planning process. Of key interest is the possibility that planning serves political interests and the material needs of an emerging municipal elite and that this is seldom acknowledged in official planning documentation or government sanctioned publications on the topic. The primary findings of the thesis are as follows: "¢ That the 'reason' of expert policy formulations that accompanied integrated development planning has weakened political economy as a prism of understanding and separated itself from the institutional reality of municipal government "¢ That the dominant critique of planning and other post-apartheid municipal policy is concerned with the triumph of neoliberalism but this critique, while valid, does not fully explain successive policy failures especially in the setting of Eastern Cape local government "¢ That function of policy and its relationship to both the state and civil society is usually understood only in the most obvious sense and not as an instrument for wielding political power "¢ That planning still derives much of its influence from its claim to technical rationality and that this underpinned the 'authority' of the integrated development planning project in South Africa and reinforced its power to make communities governable.
Keywords: Buffalo City (South Africa); Local government -- South Africa -- Eastern Cape -- Case studies; Municipal government -- South Africa -- Eastern Cape -- Case studies; Political planning -- South Africa -- Eastern Cape; Eastern Cape (South Africa) -- History -- 20th century; Eastern Cape (South Africa) -- History -- 21st century